The Effect of Advertisement, Discounts, and Game Visuals on Interest in Purchasing Cash Game Online (Case Study on Online Game Genshin Impact) - Almeira, Arlynda; Aryanto, Vincent Didiek Wiet (Jurnal Penelitian Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of advertisements, discounts, and visual games on buying interest in online cash games (Genshin Impact). The population taken in this research is new Genshin Impact players from the existing community on Twitter and Facebook. After distributing 100 questionnaires to 100 respondents, the results will be analyzed and processed. After the data is collected, the data will be analyzed through several stages, namely Validity and Reliability tests, Normality, Multicollinearity and Heteroscedasticity tests, Multiple Linear Regression Analysis, T and F tests, and the last is the Coefficient of Determination test where all of them are analyzed using IBM SPSS Statistics 25 software. The results show that advertising and visual game variables have a positive and significant effect on purchase intention, while the discount variable does not have a significant effect on purchase intention.